MEDIATORS OF THE RELATIONSHIP BETWEEN NICOTINE REPLACEMENT THERAPY AND SMOKING ABSTINENCE AMONG PEOPLE LIVING WITH HIV/AIDS - Stanton, Cassandra A. (2009)
Cigarette smoking is highly prevalent among people living with HIV/AIDS and poses unique health risks. Smoking cessation programs tailored to this population have documented improved smoking outcomes with nicotine replacement therapy (NRT). The current study examined 6-month abstinence rates from a randomized clinical trial targeting 412 HIV-positive adult current smokers (51% European American, 19% African American, and 17% Hispanic American) and tested whether psychosocial variables, such as self-efficacy and decisional balance, mediated the relationship between NRT and long-term abstinence. Meeting criteria for complete mediation, 6-month smoking abstinence rates improved significantly with increases in these mediators, and the association of NRT and smoking abstinence was no longer significant once changes in self-efficacy and decisional balance were taken into account. Failure to translate gains in self-efficacy among African Americans into improved abstinence rates accounted for racial/ ethnic differences among participants. Specific psychosocial factors, such as self-efficacy, may be particularly amenable to change in cessation interventions and should be addressed with greater awareness of how cultural and social contextual factors impact treatment response among people living with HIV/AIDS.